Ancaman Kepunahan dan Strategi Mempertahankan Warisan Budaya Takbenda Selendang Mudawaroh di Kota Palembang - Zidan, Zidan Gupara Ramdani; Ramdani, Zidan Gupara (Fakultas Adab dan Humaniora UIN Raden Fatah, 2024)
Culture is an important aspect for national life. Culture is various types of components that include knowledge, beliefs,arts, morals, laws, customs, abilities and living habits obtained by humans as members of society. Then culture willbe very important and always be close to the community. However, the biggest challenge in culture in today's societyis the rapid growth of technology that pushes local cultures such as crafts, languages, customs and traditional arts toface the threat of extinction. This threat of extinction occurs in the craft of the mudawaroh shawl which is the culturalheritage of Palembang City.The purpose of this study is to get to know more about this mudawaroh shawl craft andfind out why this craft is endangered. In this study using qualitative research types and case study approaches,research located in South Sumatra using data collection techniques in the form of interviews, observations, anddocumentation. Data analysis techniques are used with steps, data reduction, data display and conclusions. Theresults obtained in this study found factors that resulted in this craft being threatened with extinction, such as the lackof interest by the people of Palembang and the younger generation, inadequate human resources and equipment thatwas difficult to obtain. This study uses a study of public policy analysis from William Dunn to see the efforts made bythe government in cultural preservation.